Addressing knowledge gaps for transboundary environmental governance. (September 2020) - Milman, Anita; Gerlak, Andrea K.; Albrecht, Tamee; Colosimo, Mark; Conca, Ken; Kittikhoun, Anoulak; Kovács, Péter; Moy, Richard; Schmeier, Susanne; Wentling, Kelsey; Werick, William; Zavadsky, Ivan; et al.
Highlights: Knowledge gaps in transboundary settings extend beyond missing data. Knowledge gaps in transboundary settings are diverse, inter-related and compounding. Knowledge gaps may inhibit governance of transboundary resources. Distinguishing types of knowledge gaps is needed to develop strategies to fill them. Strategies to address knowledge gaps can serve to build trust and commitment. Abstract: Knowledge is widely considered a key ingredient for the effective and sustainable governance of the environment. In transboundary settings – i.e., where political boundaries cross natural resource system boundaries – there are considerable barriers to knowledge production and use. Resulting knowledge gaps can be barriers to governance. This research examines three case studies in which international river basin organizations, tasked with facilitating cooperation in transboundary river basins, recognized and addressed knowledge gaps to support governance of shared waters. We synthesize across the three case studies to develop a typology of knowledge gaps and the strategies used to address those gaps. In identifying common types of knowledge gaps and the on-the-ground strategies used to fill them, this research provides an important framework for assessing and theorizing knowledge at the transboundary scale, as well as useful recommendations and examples for practitioners seeking to develop that knowledge.